To find the solution of the system, we will set the two equations equal to each other and solve for x:
4x - 10 = -2x + 8
Add 2x to both sides:
4x + 2x - 10 = -2x + 2x + 8
6x - 10 = 8
Add 10 to both sides:
6x - 10 + 10 = 8 + 10
6x = 18
Divide by 6:
x = 3
Now that we have solved for x, we can substitute it back into one of the original equations to find the value of y:
y = 4(3) - 10
y = 12 - 10
y = 2
Therefore, the solution to the system of equations is x = 3 and y = 2.
y=4x−10 and y=−2x+8 Find the solution of the system.
1 answer